Transmitting and Translating the Excommunication of Elizabeth I - Muller, Aislinn (Studies in church history, 2017)
In 1570 Pope Pius V issued the bull Regnans in Excelsis, which excommunicated Queen Elizabeth I, deprived her of her right to rule, and released her subjects from obedience to her. This article attempts to trace the transmission of Regnans in Excelsis in the English realms during Elizabeth's reign, considering where possible the bull's publication and dispatch to different courts in Europe. It assesses efforts to distribute both publications of the excommunication, in 1570 and 1580, and what the continuity of these efforts suggests about the bull's reception amongst Elizabeth's subjects. By tracing literal translations of the bull and persistent attempts to smuggle it into the English realm, it also argues that Elizabeth's excommunication was of greater importance to her subjects than has previously been supposed.